2018
DOI: 10.24953/turkjped.2018.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric morbidity and quality of life in children and adolescents with cystic fibrosis

Abstract: Şenses-Dinç G, Özçelik U, Çak T, Doğru-Ersöz D, Çöp E, Yalçın E, Çengel-Kültür E, Pekcan S, Kiper N, Ünal F. Psychiatric morbidity and quality of life in children and adolescents with cystic fibrosis. Turk J Pediatr 2018; 60: 32-40. The aim of this study was to investigate psychiatric disorders, depression and anxiety levels, and quality of life in children and adolescents with cystic fibrosis (CF), and to compare them with those of children with non-cystic fibrosis (non-CF) bronchiectasis and healthy controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 30 publications
0
17
0
1
Order By: Relevance
“…Previous meta-analyses and systematic reviews have shown that adults and children with chronic diseases have higher risk of depression and anxiety compared to community [2,3]. A number of studies reported increased anxiety and depression in CF pateints compared to healthy controls [4][5][6]. Facing a chronic disease such as CF on a daily basis cause significant emotional burden which can be attributed to large number of treatments, hospitalizations, multiple diagnostic procedures, chronic respiratory symptoms, a lower body mass index [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous meta-analyses and systematic reviews have shown that adults and children with chronic diseases have higher risk of depression and anxiety compared to community [2,3]. A number of studies reported increased anxiety and depression in CF pateints compared to healthy controls [4][5][6]. Facing a chronic disease such as CF on a daily basis cause significant emotional burden which can be attributed to large number of treatments, hospitalizations, multiple diagnostic procedures, chronic respiratory symptoms, a lower body mass index [6].…”
Section: Introductionmentioning
confidence: 99%
“…During COVID-19 pandemic people are likely to experience fear of falling sick, dying or feelings of helplessness and a number of studies revealed a wide range of psychosocial impacts on people [4]. In a study by Wang et al, included 1210 respondents, psychological impact of the outbreak was present in 53.8%.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study of 35 children with CF ages 7 to 16 (mean 13 years) from a different Turkish center, although not reporting preadolescent findings separately, bolsters the Gundogdu data: 80% were diagnosed with ≥1 psychiatric disorder using the KSADS, significantly higher than both a control group with nonCF bronchiectasis (50%) and healthy controls (20%); anxiety (54.3%), depression (20%) and ADHD (17.1%) were most common . Given regional disparities in resources supporting the delivery of care to sustain physical and psychological functioning in individuals with CF, it is essential to consider the impact of differences in healthcare systems and culture.…”
mentioning
confidence: 97%
“…The score ranges for anxiety and depressive symptom severity in results of both PHQ-9 and GAD-7 are as follows: no symptoms (1-4), mild (5-9), moderate (10)(11)(12)(13)(14)(15), and severe (15+) symptoms. CFF/ ECFS guideline recommends supportive interventions and rescreening in the next clinical visit for patients with mild symptoms.…”
mentioning
confidence: 99%